2013
DOI: 10.1189/jlb.0112025
|View full text |Cite
|
Sign up to set email alerts
|

Leukocytes regulate retinal capillary degeneration in the diabetic mouse via generation of leukotrienes

Abstract: Understanding the early pathogenesis of DR may uncover new therapeutic targets to prevent or slow the progression of this sight-threatening disorder. We investigated the role of leukocyte-mediated generation of LTs in regulation of retinal capillary degeneration and inflammation in the diabetic mouse. We generated (1) chimeric mice that lacked the ability to generate LTs by transplanting 5LO-/- bone marrow cells into ND.WT mice and into SD.WT mice and (2) "control" chimeric mice by transplanting WT bone marrow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 41 publications
(54 citation statements)
references
References 49 publications
1
53
0
Order By: Relevance
“…A contribution of white blood cells to the pathogenesis of DR was suggested initially by evidence that diabetes-induced degeneration of retinal capillaries was significantly reduced in mice deficient in CD18 or ICAM-1 (52). The idea was further supported in mice wherein the interaction of leukocytes with endothelial adhesion molecules was blocked by neutrophil inhibitory factor (39) or mice wherein several proteins involved in inflammation or oxidative stress were deleted selectively from myeloid-derived cells (40,41). Such leukocytemediated damage to the vascular endothelial cells in diabetes has been replicated ex vivo in a co-culture system where leukocytes from diabetic or nondiabetic mice or patients were incubated with retinal endothelial cells (39,41,46).…”
Section: Abca4mentioning
confidence: 99%
See 1 more Smart Citation
“…A contribution of white blood cells to the pathogenesis of DR was suggested initially by evidence that diabetes-induced degeneration of retinal capillaries was significantly reduced in mice deficient in CD18 or ICAM-1 (52). The idea was further supported in mice wherein the interaction of leukocytes with endothelial adhesion molecules was blocked by neutrophil inhibitory factor (39) or mice wherein several proteins involved in inflammation or oxidative stress were deleted selectively from myeloid-derived cells (40,41). Such leukocytemediated damage to the vascular endothelial cells in diabetes has been replicated ex vivo in a co-culture system where leukocytes from diabetic or nondiabetic mice or patients were incubated with retinal endothelial cells (39,41,46).…”
Section: Abca4mentioning
confidence: 99%
“…Such leukocytemediated damage to the vascular endothelial cells in diabetes has been replicated ex vivo in a co-culture system where leukocytes from diabetic or nondiabetic mice or patients were incubated with retinal endothelial cells (39,41,46). Leukocytes can damage retinal endothelial cells and vasculature by releasing small lipids such as leukotrienes (35,40,62). Because leukocytes activated by lesions in one tissue can contribute to pathology at more distant sites (63,64), we considered the possibility that metabolic dysfunction or damage to the photoreceptors or RPE in diabetes could also activate leukocytes, which might then damage distant retinal vasculature.…”
Section: Abca4mentioning
confidence: 99%
“…Nevertheless, there is evidence that these inflammatory-like processes contribute to the pathogenesis of DR in both animal and patient studies, in that inhibition of proinflammatory enzymes or deletion of such enzymes inhibits diabetes-induced vascular pathology in animal models of DR. 32 Studies also have shown that leukocytes play an important role in the structural and functional abnormalities that characterize DR. 33,34 In patients, the most compelling evidence that inflammatory processes play an important role in DR pathogenesis is the dramatic effect of corticosteroids on DME. 7,35 Therefore, the specific cell types that mediate these proinflammatory effects are of great interest.…”
Section: Inflammation and Diabetic Retinopathymentioning
confidence: 99%
“…In addition, our study indicates that fenofibrate can reduce high glucose-induced cyclooxygenase-2 up-regulation to exhibit anti-inflammatory effects. 65 Aspirin has also been shown to significantly reduce the adhesiveness of leukocytes 62 and, at high doses, to minimize the development of microvascular lesions in patients in non-proliferative DR. 64,66,67 Leukocytes have been shown to play a major role in the degeneration of retinal capillaries in DR. 33,34 Leukocyte integrin a m b 2 (alias CD11b/CD18 or MAC1), a protein mediating adhesion between leukocytes and endothelial cells, has been shown to facilitate such damage to endothelial cells by activating leukocytes. 33 Diabetes causes a significant increase in leukocyte adhesion to the retinal microvasculature (leukostasis), and selective antagonism of that adhesion by expression of neutrophil inhibitory factor has been shown to inhibit the diabetes-induced degeneration of retinal capillaries.…”
Section: Anti-inflammatory Agentsmentioning
confidence: 99%
“…Leukostasis occurs in diabetic animal models [206] and in people with diabetes [207]. Adherent leukocytes can themselves damage the retinal vascular endothelium [208]. Leukocyte adherence is a biomarker of diabetic retinopathy and often used as surrogate endpoint in animal model research, as we did in demonstrating the benefit of fenofibrate in reducing retinal inflammation and diabetic retinopathy [209].…”
Section: Inflammationmentioning
confidence: 82%